Moderately Transparent Chitosan-PVA Blended Membrane for Strong Mechanical Stiffness and as a Robust Bio-Material Energy Harvester Through Contact-Separation Mode TENG - Cheedarala, Ravi Kumar; Song, Jung Il (Frontiers in Nanotechnology, 2021)
The detection of sustainable efficient resources requires for materials based on renewable en- ergies and well-organized fabrication techniques. Here, we first fabricated Chitosan-PVA (Chs- PVA) blend membranes via layer-by-layer-casting technologies. The proposed film-fabrication methods are wide-ranging, facile, ecofriendly biodegradable, mechanically, flexible, cost-ef- fective, and easy to scale up. The resultant one-step-stripped membrane was thin (4 ± 1 μm), soft, transparent, and strong, whereas the thickness of the layer-on-layer-cast membranes was 60 ± 5 μm. FT-IR analysis of the films indicated the formation of strong interactions between the amines in Chitosan and hydroxyl groups in PVA. More importantly, TEG values of ChS- PVA membranes were 3-4 orders of magnitude lower than chitosan films reported before. Layer-on- layer-cast membranes in particular exhibited high tensile strength (59.21 ± 1.12 MPa) and were more than three times stronger than other polyelectrolyte multilayer films. Both types of films remained stable in an acidic environment. Furthermore, the layer-on-layer-assembled films presented greater Voc and Isc values compared to stripped films. The developed ChS- PVA membranes can enhance impedance and TENG claims. The ChS-PVA membrane displays as a functional layer to produce charges by collecting get-up-and-go through vertical contact and separation mode TEG counter to PVDF membrane. The enhancement of Voc and Isc of ChS-PVA TEG were 244% and 1080 % from ChS TEG. Where as in the case of PVA TEG, the enhancement of Voc and Isc were increased 633% and 2888%, respectively due to due to avail- ability of free loan pair on -NH2 and -OH functional groups. The novel ChS-PVA TEG is the potential candidate for satisfying the tight requirement of optimized energy harvesting device as an alternate bio-material option for contact-separation mode TEGs.